Analysis of Hospital-Acquired Infections in a Chinese Specialized Rehabilitation Hospital: A Five-Year Surveillance Study (2020-2024) - Li Q; Wang D; Fan H (Infection and Drug Resistance)
Qianfeng Li,1 Dong Wang,1 Hanyuan Fan2 1Department of Geriatric Rehabilitation, Shenzhen Dapeng New District Nan’ao People’s Hospital, Shenzhen, People’s Republic of China; 2Hospital-Acquired Infection Control department, Shenzhen Dapeng New District Nan’ao People’s Hospital, Shenzhen, People’s Republic of ChinaCorrespondence: Hanyuan Fan, Hospital-acquired infection control department, Shenzhen Dapeng New District Nan’ao People’s Hospital, No. 6 Renmin Road, Nanao Street, Dapeng New District, Shenzhen, 518100, People’s Republic of China, Tel +86-13760331505, Email fanhanyuan25@163.comObjective: Hospital-acquired infections (HAIs) pose significant challenges in rehabilitation hospitals, particularly affecting patients with extended stays and complex medical needs. This study analyzed HAI patterns and risk factors in a Chinese rehabilitation hospital from 2020 to 2024.Methods: A retrospective observational study was conducted at a tertiary-care rehabilitation hospital with 25 specialized wards. Data collection included patient demographics, clinical parameters, and ward-level characteristics. Statistical analysis employed Poisson and Quasi-Poisson regression models to identify risk factors, with comprehensive diagnostic evaluation.Results: The study revealed an overall infection rate of 3.64%, representing 385 infections among 10,559 inpatients. The Vegetative State Awakening Department exhibited the highest infection rate at 11.1%, followed by Geriatric Rehabilitation Department (8.2%), and Neuro Rehabilitation Department wards (5.5– 7.0%). Respiratory tract infections were most common (42%), with ventilator-associated pneumonia accounting for 28% of all infections. Statistical analysis identified several significant risk factors through both Poisson and Quasi-Poisson regression models. In the more reliable Quasi-Poisson model that accounted for overdispersion, tracheal intubation emerged as the strongest predictor with a coefficient of 2.02 (p < 0.001), followed by use of glucocorticoids (coefficient: 1.78, p < 0.001). While the initial Poisson model suggested a protective effect of radiation therapy, this effect was not significant in the Quasi-Poisson model.Conclusion: The study highlights the critical role of tracheal intubation and glucocorticoid use in HAI development within rehabilitation settings. The significant ward-level variability in infection rates suggests the need for tailored infection control strategies. Implementation of targeted interventions focusing on these identified risk factors could help reduce HAI incidence in rehabilitation hospitals.Keywords: hospital-acquired infections, rehabilitation hospital, risk factors, infection control, healthcare surveillance, China, nosocomial infections, patient safety